Creatine kinase increases in adults with uncontrolled hypertension - Andy Luman; Abdurrahim Rasyid Lubis (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUND A substantial proportion of uncomplicated, treated primary hypertensive patients have failure of hypertension treatment. The enzyme creatine kinase (CK) regenerates adenosine triphosphate in striated muscle, myocardium and blood vessels. Several studies showed that serum CK was found to be a predictor of blood pressure in the general population. High tissue CK precedes hypertension in populations with high hypertension risk. The hypothesis of this study was to examine that CK increases in uncontrolled hypertension subjects. METHODS A cross-sectional study from November until December 2013 was conducted in 82 adult hypertensive patients with mean age of 61.96 ± 10.76 years. Patients’ histories were taken and their blood pressure and body mass index were measured. Serum was analyzed for serum CK, random blood glucose and lipid profile. Independent t test and Mann Whitney was used to assess differences in mean CK and other variables between hypertension categories. Chi-square test was also used to assess differences between CK tertiles and status of hypertension. RESULTS There was a significant difference in mean CK between controlled hypertension (81.83 ± 29.70 U/L) and uncontrolled hypertension groups (132.17 ± 55.91 U/ L). The number of subjects in the high CK tertile (>109.33 U/L) was significantly higher in the uncontrolled hypertension group (81.5%), compared with the controlled hypertension group (18.5%) (p=0.0001). CONCLUSION Creatine kinase level increases in adults with uncontrolled hypertension. Measuring serum levels of creatine kinase may help doctors to spot patients whose hypertension will be difficult to treat.